2005
DOI: 10.1143/jjap.44.1641
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Study of Double-Walled Carbon Nanotubes for Nano-Mechanical Manipulation

Abstract: Double-walled carbon nanotubes (DWNTs) are expected to be useful as elements in nano-mechanical systems such as nanobearings and nanosliders. A molecular dynamics simulation is carried out to estimate the relative motion between the inner and outer tubes. The force required to pull the inner tube out of the outer tube is evaluated quantitatively by pulling the inner tube under a constant velocity for DWNTs with various inter-tube spacings and chiralities. When the inner tube is pulled under smaller constant fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Although, the axial vibration of SWCNTs with uniform and nonuniform cross-sections was studied using the nonlocal continuum models (Aydogdu, 2009a;Danesh et al, 2012) to the best of the author's knowledge, the axial vibration of MWCNT has not been considered in the previous studies. As mentioned in the previous studies (Kimoto et al, 2005;Dong et al, 2006;Zhao and Cummings, 2006) axial vibration of DWCNTs is important for nanoscale linear motors, gigahertz nanooscillators, or nanoscale damped springs. So, the main objective of this study is to fill this gap in the literature.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Although, the axial vibration of SWCNTs with uniform and nonuniform cross-sections was studied using the nonlocal continuum models (Aydogdu, 2009a;Danesh et al, 2012) to the best of the author's knowledge, the axial vibration of MWCNT has not been considered in the previous studies. As mentioned in the previous studies (Kimoto et al, 2005;Dong et al, 2006;Zhao and Cummings, 2006) axial vibration of DWCNTs is important for nanoscale linear motors, gigahertz nanooscillators, or nanoscale damped springs. So, the main objective of this study is to fill this gap in the literature.…”
Section: Introductionmentioning
confidence: 86%
“…In this study axial effects of van der Waals forces were considered. Kimoto et al (2005) used a molecular dynamic simulation to estimate the relative motion between the inner and outer tube of a double-walled carbon nanotube (DWCNT). The force required to pull the inner tube out of the outer tube was obtained.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the magnitude of the pull-out force depends on the relative distance between nanotubes or graphene layers at the exit position [32]. By considering the direction of sliding motion as a positive reference, pull-out forces are negative for transitions from stable to unstable/metastable conditions (i.e., the sliding motion is energetically unfavorable and an external force is required to pull out the nanoconstruct), while they are positive in the opposite case.…”
Section: Introductionmentioning
confidence: 99%
“…Rafii-Tabar 4 reviewed computational modeling works of transport properties inside carbon nanotubes. Carbon nanostructures such as fullerene, diamondiod, and nanotubes have been considered as the promising materials for the realization of nanomachines: fullerene nano ball bearings, 5 6 nanotube needle bearings, 7 nanotube gears, 8 9 nanotube drills, 11 nanotube motors, 8 9 12-17 nanotube oscillators, [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] nanotube pipette, 37−39 nanotube nozzle, 40 nanotube electromechanical oscillators, 41 etc. Merkle 42 discussed the symmetry properties of molecular bearings.…”
Section: Introductionmentioning
confidence: 99%
“…29 30 As mentioned above, the CNT oscillators based on multi-walled CNTs have been widely investigated using the MD simulations. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] How to initialize these devices in a controllable way has been investigated. Legoas et al 24 25 showed that initialization of these systems could be achieved by applying an external electric field, injecting a charge, or applying variable magnetic fields, using internal metallic (or filled with metallic materials) and external semiconducting nanotubes.…”
Section: Introductionmentioning
confidence: 99%